1991
DOI: 10.1002/hrdq.3920020106
|View full text |Cite
|
Sign up to set email alerts
|

Organizational training and signals of importance: Linking pretraining perceptions to intentions to transfer

Abstract: Note: The authors would like to thank Michael Zeller and Mark Gavin for their assistance on this project, HUMAN m m c~ DEVE~PMENI QUARTERLY, WL 2. no. 1. Spring 1991 @ J o s u y -k Inc.. Publishers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 18 publications
5
98
0
1
Order By: Relevance
“…In the context of mandatory training, researchers have been mostly interested in investigating the effectiveness of training programs as well as employees' pre and post training motivation (Colquitt, LePine and Noe 2000). With respect to participation, some studies have investigated the impact of the choice to participate on motivation, learning and other variables (Baldwin and Magjuka 1991;Cohen 1990;Hicks and Klimoski 1987) as well as the relationship between motivation and participation in training and development (Tharenou 2001). …”
Section: Stéphane Renaud Mehdi Lakhdari Lucie Morinmentioning
confidence: 99%
“…In the context of mandatory training, researchers have been mostly interested in investigating the effectiveness of training programs as well as employees' pre and post training motivation (Colquitt, LePine and Noe 2000). With respect to participation, some studies have investigated the impact of the choice to participate on motivation, learning and other variables (Baldwin and Magjuka 1991;Cohen 1990;Hicks and Klimoski 1987) as well as the relationship between motivation and participation in training and development (Tharenou 2001). …”
Section: Stéphane Renaud Mehdi Lakhdari Lucie Morinmentioning
confidence: 99%
“…Studies show that the motivation to learn and a positive pre-training attitude positively correlate with the amount of learning that occurs (Baldwin and Magjuka, 1991;Tannenbaum, Mathieu, Salas, & Cannon-Bowers, 1991). Baldwin, Magjuka & Loher (1990) found that the level of pre-training motivation increases when the training is perceived as mandatory (thus challenging a widely held assumption), and when the learner has an expectation of posttraining accountability to management.…”
Section: Intention To Transfermentioning
confidence: 99%
“…More recently, the interest in numerous work-environment characteristics has grown. Researchers (Baldwin & Magjuka, 1991;Tracey, Tannenbaum, & Kavanagh, 1995;Elangovan & Karakowsky, 1999;Kontoghiorghes, 2001) have recognized the importance of several environmental characteristics and have examined variables outside the immediate training program that may be important to the success of the training effort.…”
mentioning
confidence: 98%